2020
DOI: 10.1039/d0sm00932f
|View full text |Cite
|
Sign up to set email alerts
|

Collapse and cavitation during the drying of water-saturated PDMS sponges with closed porosity

Abstract: In this paper, we study the drying of water-saturated porous polydimethylsiloxane (PDMS) elastomers with closed porosity in which the evaporation of water is possible only via the diffusion across the...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Such pore opening phenomena during drying have also been observed during drying of other soft porous materials ( Nguyen et al, 2020 ). Such phenomena are investigated theoretically ( Wang and Cai, 2015a , 2015b ), where a constrained hydrogel with central cavity is subject to dehydration.…”
Section: Introductionsupporting
confidence: 56%
“…Such pore opening phenomena during drying have also been observed during drying of other soft porous materials ( Nguyen et al, 2020 ). Such phenomena are investigated theoretically ( Wang and Cai, 2015a , 2015b ), where a constrained hydrogel with central cavity is subject to dehydration.…”
Section: Introductionsupporting
confidence: 56%
“…In the 'high Ca El ' series, the capillary pressure in the droplets is always lower than the storage modulus of the continuous phase in the range of frequencies we explored, leading to a consistently softening tendency. For the 'low Ca El ' series, measurement of droplet size is difficult, as is a risk of collapse of empty pores in the soft matrix upon sectioning the sample for microscope observation, which was also observed by Nguyen et al [37]. As a consequence, it is possible that the real size distribution in the samples diverges from the measured distribution, most notably with more smaller droplets than expected.…”
Section: Comparison To Modelsmentioning
confidence: 91%
“…As the pH was maintained constant for both substrates, it may be confidently concluded that these features are a result of the different DLVO forces at play in both these cases. Cavitation has been observed in drying droplets of colloidal solutions and gels [44,45], and occurs due to variation of osmotic pressure between pores, enclosing shell and surrounding liquid drop. In porous samples as in gel networks like Laponite ® gel, if evaporation from bubbles trapped inside gels walls takes place faster than diffusion of solute from the bubble interface to its interior, a cavity may be created inside the gel drop.…”
Section: Cavitation In Acidic Ph On Hydrophobic Substratementioning
confidence: 99%